Children as Perpetrators of Narcotics Abuse In Criminology Perspective (North Morowali Police Study) - Ahmad Sadat; Andi Purnawati; Irmawaty (Indonesian Research Journal in Legal Studies, 2022)
This study aims to determine the factors that influence children to commit narcotics crimes and to identify and analyze the efforts of the North Morowali Police in dealing with narcotics crimes committed by children. This type of research is empirical research, namely research with field data as the main data source, such as the results of interviews and observations. In terms of its nature, this research is a descriptive research. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The results of the study found that the factors that cause children to abuse narcotics are internal factors and external factors. Internal factors are factors that come from within oneself, while external factors are factors that come from outside themselves and the efforts of the North Morowali Resort police in overcoming Narcotics crimes committed by children, namely using 3 (three) efforts, namely pre-emptive efforts (coaching), preventive efforts (prevention), and repressive efforts (actions). The research suggestion is that the existing law be revised again and make it clearer about children involved in narcotics abuse and efforts to overcome juvenile delinquency who use narcotics must prioritize preventive actions where these efforts must be emphasized from the age of children to their teens.